Development of the Parasitoid Trichogramma Sp. and Its Parasitization Capability Population Pest Spodotera Furgiperda in Plantation Corn Please, Tomohon City - Lengkong, Maxi; Dien, Moulwy F.; Paruntu, Meisye H. B. (Budapest International Research and Critics University, 2024)
Spodoptera frugiperda is a new pest that entered Indonesia around 2018 and acts as the main pest that causes young corn plants to be damaged and experience growth problems. It is known that there is a natural enemy, namely the parasitoid Trichogramma sp. which can attack S. frugiperda eggs. The research method can be carried out by experimenting with the development and multiplication of the parasitoid Trichogramma sp. in the laboratory using a previously cultured population of C. cephalonica eggs as a host. The results showed that the multiplication of the egg parasitoid Trichogramma sp. with alternative host C. cephalonica can be done in the laboratory. Biological development in the form of the life cycle of the parasitoid Trichogramma sp. can be known based on observations, namely the egg stage is around 14-15 hours, the first instar larva stage is 22 hours, the second instar is 24 hours, the third instar is 25 hours, the fourth instar is 26 hours, the pupa stage is 28 hours, the lifespan of adult female insects is 10-12 days while the male 10-11 days. Percentage of parasitization of Parasitoid Trichogramma sp. the population of the S. frugiperda pest egg group in the field was quite high, ranging from 68.5 – 87.3 percent with an average of 76.5 percent.